Sensitive skin syndrome: Research progress on mechanisms and applications - Chuanxia Jiang; Chaowan Guo; Jipeng Yan; Jie Chen; Shujing Peng; Haishu Huang; Weizhi Wu; Yanfeng Nie; Yunlin Pei; Huaiqing Sun (Journal of Dermatologic Science and Cosmetic Technology)
Sensitive skin is a clinical syndrome characterized by a hyper-reactive state of the skin, primarily on the face. It is accompanied by subjective symptoms such as burning, stinging, itching, and tightness when exposed to physical, chemical, or psychological stimuli. Objective signs, such as erythema, scales, and dilated blood vessels, may or may not be present. The discomfort associated with sensitive skin can be triggered by various endogenous and exogenous factors, which usually have no significant effect on the individual and do not induce irritant reactions. Sensitive skin often presents as a subjective state without clinical signs and exhibits diversity, posing challenges in sensitive skin research and care. This review summarizes the prevalence, key factors, pathophysiological mechanisms, diagnosis, and progress in daily care for sensitive skin. The aim is to provide a clearer and more systematic understanding of sensitive skin and offer guidance for sensitive skin care.